Wound Treatment with Moist Dressing Technique Using Nacl 0.9% And Garamysin On The Number Of Bacterial Colonies - Rahayu, Sri Mulyati (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study investigates the effects of moist dressing techniques using 0.9% NaCl and Garamycin on bacterial colony counts in diabetic gangrene wounds. Diabetic ulcers represent a significant challenge in wound management, as improper treatment can lead to severe complications, including infection and amputation. A controlled experimental approach was employed, utilizing diabetic rats induced with alloxan to establish hyperglycemia. The treatment group received moist dressings with 0.9% NaCl and Garamycin over seven days, while bacterial colony counts were assessed before and after treatment. Results indicated a significant reduction in bacterial colonies from an average of 291.625 to 69.75 post-treatment, demonstrating the effectiveness of the combined treatment in preventing bacterial growth. This reduction underscores the importance of maintaining a moist environment for wound healing and the role of antibacterial agents in managing diabetic wounds. The findings contribute valuable insights into optimal wound care practices, emphasizing the need for appropriate dressing selection to enhance healing outcomes and minimize infection risks.